FEASIBILITY STUDY PEMBANGUNAN HOTEL DI DESA KUTUH, KECAMATAN KUTA SELATAN, KABUPATEN BADUNG - Ida Ayu Eka Pramita; Ni Luh Putu Wiagustini (Journal of Applied Management Studies, 2020)
The Badung Regency Government plans to build a Starred Hotel on land owned by Kutat Adat Village, on the grounds that tourism in the Kutuh Village is just developing. Desa Kutuh is expected to become an integrated Tourism Region through its natural charm and various Balinese Cultural attractions that are displayed. In connection with the plan, a feasibility study is needed for the investment in hotel construction in the village of Kutuh. There are seven aspects examined in this study, namely (1) Aspects of regional potential; (2) Legal aspects; (3) Market Aspects; (4) technical aspects; (5) Aspects of Human Resource Management; (5) Financial aspects. Data and information are collected through observation, interviews and documentation, then analyzed with descriptive and qualitative analysis techniques. The analysis shows that Kutuh Village has tourism and accommodation potential that is possible to be developed by building a Four Star hotel. Judging from the legal aspects of investment in hotel construction in the village of Kutuh, supported by the Law and Regional Government Regulation. The hotel that will be built has a market opportunity with medium competitiveness and medium category appeal, so it can be said to be feasible from the marketing aspect. The estimated investment needed is Rp161,874,034,000, - for a four-star hotel, the hotel must be managed by a professional, so that the right organizational structure is a functional organizational structure that is divided into departments. Based on the financial aspects of the construction of the Four Star Hotel, it is feasible to continue in Kutuh Village if the maximum is to use 50% debt, a 10-year tenor of 10% interest rate with a minimum hotel occupancy rate of 37% per year.